Current pattern of presentation and approach to the management of ectopic gestation in the state specialist hospital Ondo: a two-year review - Adegoke, Adedokun I. (International Journal of Research in Medical Sciences, 2017)
Background: Ectopic gestation is still the leading cause of pregnancy related death in the first trimester. Not much has changed in the area of management in the developing world due to the pattern of patients’ presentation and paucity of laparoscopic facilities. The study aims to assess the current pattern of presentation and approach to the management of ectopic gestation in a secondary health facility in sub-Saharan Africa. Methods: A retrospective study was carried out to assess the current pattern of patients’ presentation and approach to management of ectopic gestation in State Specialist Hospital, Ondo, Nigeria. All the data were retrieved from the case record of patients and analysed using SPSS version 20. Result: The commonest symptoms patients presented with were abdominal pain, amenorrhoea and vaginal bleeding with figures 63 (96.92%), 47 (72.31%) and 34 (52.31%) respectively. Tubal ectopic gestation was the commonest type found in 60 (92.31%) patients and was more on the right (56.92%). Fifty-nine (90.77%) of the tubal ectopic gestations were ruptured while only one was unruptured. All the patients had exploratory laparotomy. No mortality was recorded during the period under review. Conclusion: All the patients reviewed had exploratory laparotomy mainly due to the non-availability of laparoscopy in our centre, the nature of presentation and the financial capability of the patients and their relations. These factors still remain the determinants of clinician’s choice of patients’ management in low resource settings of the world.